A construção da autonomia na gestante e a contribuição da abordagem centrada na pessoa na preparação do parto humanizado - Baretta, Melissa Grazielly (2022)
The insertion of Psychology, as a science and profession, aims to accommodate the demands of pregnant women in the process of preparing for childbirth and birth, the entry of Psychology in the humanization process approaches the relationships woven between people, very far from the technological reality that is permeating the birth scene today. The routine use of cesarean sections as a method of delivery was discussed by the authorities responsible for world health, the World Health Organization (WHO), which clarifies in the WHO Declaration on Cesarean Rates, in 2015, that cesarean delivery is the intervention that should save the mother and baby's lives when properly indicated. This makes us question the sad reality regarding the abusive practice of cesarean section, especially in Brazil, where the WHO's indicative numbers exceed what is proposed and advised (15%), occupying the 2nd place among the countries in the world that most performs such a procedure. procedure. Therefore, this research uses the Intervention Research methodological procedure that stimulates the researcher-participants relationship, through the exercise of interaction, for the understanding of the social reality in the face of the researched theme. The theoretical and methodological framework used in the research was the Person-Centered Approach, a strand of Humanistic Psychology proposed by Carl Rogers in the 1940s. The research was carried out with a pregnant woman assisted by the Tijucal Health Center, located in the city of Cuiabá. The calls took place remotely through video call by application, due to the influence of the pandemic scenario caused by Sars-CoV-2 (Covid-19). In all, six consultations were carried out, all guided by the aspects involved in the experience with the pregnant woman participating in the research. The objective of the research was to investigate the impact of psychological listening for women during the preparation for childbirth, childbirth and motherhood, aiming to foster the construction of female autonomy. As secondary objectives, we sought to understand the subjectivities arising from the woman's experience and her pregnancy, as well as her perceptions of feelings, as she perceived herself in this moment of pregnancy and preparation for the delivery and birth of the child. The research findings were discussed from the PCA perspective, through which it was possible to approach the researcher's experiences in the experience of the intersubjective relationship with the pregnant woman, thus expressing the feelings and meaning of the experience. The results were presented in the form of axes of meanings and meanings, as follows: Axes of meanings of Psychological Counseling in Preparation for Childbirth; Axes of meaning and meanings of women's experience during pregnancy. It was concluded that Psychological Accompaniment is a facilitating intervention for the construction of autonomy, as well as a space for the promotion and attention of psychic health.